Nutritional Status in Patients with Major Depressive Disorders: A Pilot Study in Tabriz, Iran - Bahram Pourghassem Gargari; Maryam Saboktakin; Soltanali Mahboob; Nosratollah Pourafkari (Health Promotion Perspectives, 2012)
Introduction: This study was conducted to assess the nutritional status in Iranian major depres-sive disorder patients. We also determined the relationship between nutrients intake with depres-sion severity.Methods: Seventy major depressive patients were selected randomly from outpatient depressive subjects, referred to Razi Psychiatry Hospital in Tabriz, Iran in 2007. Dietary intakes were rec-orded and compared with dietary reference intakes (DRIs). Definition of the disease and its se-verity were according to DSM-IV-TR and Hamilton Depression Rating Scale, respectively. Nu-tritionist III program, Chi-square, correlation and t-test were used for data analyses. Demo-graphic, clinical and laboratory data were analyzed using SPSS software for windows (ver-sion13.0).Results: According to dietary analysis, 11.4% and 55% of patients had dietary protein and energy deficiency, respectively. 97.1% and 95.7% of patients had less folate and B12 intakes than recom-mended dietary allowances. The mean (Mean ± SD) for plasma folate and B12 was 5.18±6.11 ng/ml and 389.05±346.9 pg/ml, respectively. Low plasma folate and B12 was observed in 51.4% and 50.0 % of patients, respectively. There was no significant relationship between blood folate and B12 levels with depression severity. Similarly, nutrients intake had no effect on depression se-verity.Conclusions: Low plasma concentrations and low dietary intakes of folate and B12 are common among Tabrizian depressive patients. It seems that nutritional intervention for increasing folate and vitamin B12 intake must be considered as health promotive and preventative program for pa-tients suffering from depression disorders.